The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3390/coatings9100660
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cathodic Arc Guiding Magnetic Field on the Growth of (Ti0.36Al0.64)N Coatings

Abstract: We use a modified cathodic arc deposition technique, including an electromagnetic coil that introduces a magnetic field in the vicinity of the source, to study its influence on the growth of (Ti0.36Al0.64)N coatings. By increasing the strength of the magnetic field produced by the coil, the cathode arc spots are steered toward the edge of the cathode, and the electrons are guided to an annular anode surrounding the cathode. As a result, the plasma density between the cathode and substrate decreased, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…At atmospheric pressure, optical emission spectrometry is practically the only method for revealing the elemental composition of the discharge plasma. Therefore, in the case of a vacuum arc [28], studying the dependence of the spectral energy density on the radiation wavelength provides detailed information about the presence in the plasma of both positive ions and neutral atoms [29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…At atmospheric pressure, optical emission spectrometry is practically the only method for revealing the elemental composition of the discharge plasma. Therefore, in the case of a vacuum arc [28], studying the dependence of the spectral energy density on the radiation wavelength provides detailed information about the presence in the plasma of both positive ions and neutral atoms [29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…Some potential experimental instruments that can study neutral species in the plasma are massenergy analyzer (MEA, see Chapter 5.1.2.) in RGA mode and optical emission spectroscopy [114,115].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a magnetic field can be used to guide the motion of ions [11][12][13][14][15][16][17]. Magnetic fields were commonly used to control the motion of cathode spots [12][13][14], and were also introduced to guide ion motion and to remove the macro-particles from the arc source [15][16][17]. Therefore, controlling the movement of deposition ions may be beneficial for the deposition of inner surface coating.…”
Section: Introductionmentioning
confidence: 99%